General Symmetric Starter of Orthogonal Double Covers of Complete Bipartite Graph - R. A. El-Shanawany; M. Sh. Higazy (International Journal of Mathematics and Mathematical Sciences)
An orthogonal double cover (ODC) of the complete graph is a collection of graphs such that every two of them share exactly one edge and every edge of the complete graph belongs to exactly two of the graphs. In this paper, we consider the case where the graph to be covered twice is the complete bipartite graph Kmn,mn (for any values of m,n) and all graphs in the collection are isomorphic to certain spanning subgraphs. Furthermore, the ODCs of Kn,n by certain disjoint stars are constructed.